Use of organic materials in dye-sensitized solar cells - Lee, Chuan-Pei; Li, Chun-Ting; Ho, Kuo-Chuan (Materials today (Kidlington, England), 2017)
In the last two decades, dye-sensitized solar cells (DSSCs) have attracted more attention as an efficient alternative to economical photovoltaic devices, and the highest efficiency record has increased from ∼7% to ∼14%. To be more competitive in the solar cell markets, various organic materials are investigated and used in DSSCs to improve the cell efficiency, enhance the cell durability, and reduce the cost of production. In this review article, we provide a short review on the organic materials used for the preparation of photoanodes (including metal element-free organic dye sensitizers), quasi/all-solid-state electrolytes, and metal element-free electrocatalytic films in DSSCs with the cell efficiencies of >5%. Finally, the future perspectives for DSSCs are also briefly discussed.